Missed Opportunities for Concurrent HIV-STD Testing in an Academic Emergency Department. (January 2014) - Klein, Pamela W.; Martin, Ian B.K.; Quinlivan, Evelyn B.; Gay, Cynthia L.; Leone, Peter A.
Objectives: We evaluated emergency department (ED) provider adherence to guidelines for concurrent HIV-sexually transmitted disease (STD) testing within an expanded HIV testing program and assessed demographic and clinical factors associated with concurrent HIV-STD testing. Methods: We examined concurrent HIV-STD testing in a suburban academic ED with a targeted, expanded HIV testing program. Patients aged 18–64 years who were tested for syphilis, gonorrhea, or chlamydia in 2009 were evaluated for concurrent HIV testing. We analyzed demographic and clinical factors associated with concurrent HIV-STD testing using multivariate logistic regression with a robust variance estimator or, where applicable, exact logistic regression. Results: Only 28.3% of patients tested for syphilis, 3.8% tested for gonorrhea, and 3.8% tested for chlamydia were concurrently tested for HIV during an ED visit. Concurrent HIV-syphilis testing was more likely among younger patients aged 25–34 years (adjusted odds ratio [AOR] = 0.36, 95% confidence interval [CI] 0.78, 2.10) and patients with STD-related chief complaints at triage (AOR=11.47, 95% CI 5.49, 25.06). Concurrent HIV-gonorrhea/chlamydia testing was more likely among men (gonorrhea: AOR=3.98, 95% CI 2.25, 7.02; chlamydia: AOR=3.25, 95% CI 1.80, 5.86) and less likely among patients with STD-related chief complaints at triage (gonorrhea: AOR=0.31, 95% CI 0.13, 0.82; chlamydia: AOR=0.21, 95% CI 0.09, 0.50). Conclusions: Concurrent HIV-STD testing in an academic ED remains low. Systematic interventions that remove the decision-making burden of ordering an HIV test from providers may increase HIV testing in this high-risk population of suspected STD patients.